ESTABLISHMENT OF A RAT MODEL OF TEMPOROMANDIBULAR JOINT OSTEOARTHRITIS USING INTRAARTICULAR INJECTION OF COMPLETE FREUND’S ADJUVANT - Dwi Merry Christmarini Robin (UNEJ e-Proceeding)
Osteoarthritis is a common progressive joint disease,involving not only the joint lining but also cartilage,ligaments, and bone. Osteoarthritis (OA) of thetemporomandibular joint is a unilateral,degenerative disease of the jaw joint. It ischaracterized by breakdown of the articularcartilage, architectural changes in bone, anddegeneration of the synovial tissues causing painand/or dysfunction in functional movements of thejaw. Temporomandibular joint osteoarthritis (TMJOA) is an important etiology of temporomandibularpain. The temporomandibular joint (TMJ) undergoesdegenerative changes among patients who sufferfrom arthritis, and yet the pathogenesis of TMJosteoarthritis and rheumatoid arthritis is poorlyunderstood. However, until recent years, OA of thetemporomandibular joint was confusing, relativelyunrecognized, and difficult to diagnose and manageand the specific mechanisms of TMJ OA in thedevelopment of temporomandibular pain are stillnot clear. Animal models are useful tools for theinvestigation of association between animalbehavioral and TMJ OA. Several animal models ofTMJ OA have been established using intraarticularinjection of various chemicals. This study aimed toestablish a rat model of TMJ OA using completeFreund’s adjuvant (CFA). Histopathological changewith hematoxylin-eosin staining and radiographicchange of the TMJ was performed. Treatment withCFA induced cartilage damage, synovitis, andproliferation of synovial cells in the fact joints. A ratmodel of TMJ OA was successfully established usingintraarticular injection of CFA. This animal model isconvenient and shows good resemblance to humanOA pathology. We hypothesized that inflammationin the TMJ induces structural abnormalities, andaccordingly characterized the disc and synovium in anovel model with double injections of completeFreund’s adjuvant (CFA), using histopathologicalchange with hematoxylin-eosin staining andradiographic examinition.